DAMPAK IMPOR DAN EKSPOR JAGUNG TERHADAP PRODUKTIVITAS JAGUNG DI INDONESIA - Susilo Utomo (Faculty of Economic and Business, 2012)
The aim of this research is to analyze the impact of corn’s net export to the corn productivity in Indonesia. This research used the quantitative methods with two stage least square method. In this research, the statistical criteria to validate the econometric model predicted value were using root means square errors (RMSE), root means squares percent error (RMSPE) and theil’s inequality coefficient (U). The result shown that domestic corn price, world corn price, and exchange rate influence to corn export and impor in Indonesia. The corn export and import value give an influence to corn productivity in IndonesiaDOI: 10.15408/etk.v11i2.1891